2019
DOI: 10.1108/jcm-04-2017-2165
|View full text |Cite
|
Sign up to set email alerts
|

Developing brand emotions across cultures: effects of self-construal and context

Abstract: Purpose The purpose of this paper is to study the nature of brand emotions elicited by advertising stimuli across cultures and the process underlying such emotional experiences. Design/methodology/approach The study uses factorial between-subjects design. Random samples of the populations were solicited from the panels of an international data provider in Norway and Thailand. Findings This research shows that Thai consumers experience more positive socially engaging and disengaging brand emotions and fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…That is, secure and anxious attachment styles weaken and strengthen the negative impact of service failure severity on brand forgiveness, whereas an avoidant attachment style plays no significant role. Fourth, prior branding research has shown that thinking styles are valid concepts for understanding the elicitation of salient brand emotions (Jakubanecs et al , 2019), consumers’ reactions to brand extensions (Allman et al , 2019) and brand placement (Hur et al , 2020). Our study also adds to this by showing that holistic and analytic thinking are also valid concepts in service failure contexts: the former weakens, and the latter strengthens, the negative impact of service failure severity on brand forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…That is, secure and anxious attachment styles weaken and strengthen the negative impact of service failure severity on brand forgiveness, whereas an avoidant attachment style plays no significant role. Fourth, prior branding research has shown that thinking styles are valid concepts for understanding the elicitation of salient brand emotions (Jakubanecs et al , 2019), consumers’ reactions to brand extensions (Allman et al , 2019) and brand placement (Hur et al , 2020). Our study also adds to this by showing that holistic and analytic thinking are also valid concepts in service failure contexts: the former weakens, and the latter strengthens, the negative impact of service failure severity on brand forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Third, while soccer merchandise was ideal for assuring cultural relevancy for the Hispanic market, the research failed to account for the potential influence of the Hispanic shopper’s involvement level with this category. Similarly, given the influence culture has in determining consumers’ behaviors (Cakanlar and Nguyen, 2019; Jakubanecs et al , 2019), this research could be enriched by incorporating Hofstede’s (1980) cultural values to assess their influence on Internet-related behaviors and potential differences across subgroups of online immigrant consumers. Finally, while this study is among the very first to examine the roles of ethnic identity and gratitude in driving online loyalty in an immigrant population, we measured behavioral intentions rather than actual purchase and word-of-mouth behaviors, presenting an opportunity to further examine these issues.…”
Section: Discussionmentioning
confidence: 99%
“…This may mean that BESC as an individual tendency will also depend on culture or socioeconomic context. Indeed, according to Markus and Kitayama's (1991), Self Construal Theory, culture determines self-construal and individuals from different cultures have reliable differences in self-construal (Jakubanecs et al, 2019).…”
Section: Brand Engagement In Self-conceptmentioning
confidence: 99%